Developing a Measure of Living Standards for Elders in New Zealand - Breheny, Mary; Stephens, Christine; Mansvelt, Juliana; Horrell, Barbara (Massey University, 2011)
No abstract
Author manuscript
Keywords: Standard of living; Older people